Insights into different nitrate formation mechanisms from seasonal variations of secondary inorganic aerosols in Shanghai. (November 2016) - Tao, Ye; Ye, Xingnan; Ma, Zhen; Xie, Yuanyuan; Wang, Ruyu; Chen, Jianmin; Yang, Xin; Jiang, Shuqin
Abstract: The dominant mechanisms for the formation of fine particulate nitrate during four seasons were proposed by evaluating the correlations between [NO3 − ]/[SO4 2− ] and [NH4 + ]/[SO4 2− ]. Size-resolved aerosols were collected in Shanghai from April 2013 to January 2014. The concentration of fine particulate nitrate was below one tenth of the concentration of sulfate in summer, whereas fine particulate nitrate dominated over sulfate in winter. Influenced by aged sea salt aerosols, the molar ratio of [Na + ]/[NH4 + ] reached 53 ± 49% and the depletion of chloride was very significant (0.83) during autumn. In spring, the increase of nitrate concentration became evident for [NH4 + ]/[SO4 2− ]>2, indicating that sulfate is fully neutralized. During summertime, nighttime hydrolysis of N2 O5 dominated the fine particulate nitrate formation. The thresholds of [NH4 + ]/[SO4 2− ] for nitrate formation in autumn and winter were wrongly characterized by the linear regression between [NO3 − ]/[SO4 2− ] and [NH4 + ]/[SO4 2− ], because considerable amounts of Na2 SO4 and NH4 Cl were present. Replaced by free ammonium in the function equation, it was established that the winter and spring aerosols shared the same nitrate formation mechanism. On the basis of free sulfate, it was evident that both homogeneous neutralization and hydrolysis of N2 O5 mechanisms were involved during autumn. Graphical abstract: Highlights: Seasonal perspective of nitrate formation mechanism in Shanghai is reported. Excess and depletion of chloride are observed in the polluted coastal city. Nitrate formation mechanism should be carefully proposed under maritime regime.